Development of Mobile Sanitizing Robot in Operation Rooms - Adam, Nur Auni; Omar, Rosli (Evolution in Electrical and Electronic Engineering, 2023)
Nowadays, technology gives a huge positive impact on dealing with the covid-19 pandemic. Accordingly, the field of robotics and control automation has become a phenomenon due to the availability of robot technology that can help daily human activities. Thanks to the robots that are able to replace human tasks to perform human work fast and effectively. This report outlines how to build a mobile sanitizing robot in the operating room to reduce the staff of doctors and nurses’ burden during duty. In this project, the robot is developed using electronic components such as Arduino Mega 2560, L298N Motor Driver, IR Sensor Module and Ultrasonic Sensor Module. Precisely, this robot uses UV-C rays to replace liquid sanitation. The mode used in this project is automatic mode. The automatic mode used is based on the concept of Line Following. UV-C has a short-wave frequency with a peak wavelength of 253.7nm. However, improvements are needed to improve and optimize the functionality of this robot. For example, the duration of Irradiation of UV-C rays and the speed of the motor can be changed to control the duration of the movement.